Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/biolre/iox174
|View full text |Cite
|
Sign up to set email alerts
|

Gestational restricted- and over-feeding promote maternal and offspring inflammatory responses that are distinct and dependent on diet in sheep†

Abstract: Inflammation may be a mechanism of maternal programming because it has the capacity to alter the maternal environment and can persist postnatally in offspring tissues. This study evaluated the effects of restricted- and over-feeding on maternal and offspring inflammatory gene expression using reverse transcription (RT)-PCR arrays. Pregnant ewes were fed 60% (Restricted), 100% (Control), or 140% (Over) of National Research Council requirements beginning on day 30.2 ± 0.2 of gestation. Maternal (n = 8-9 ewes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…Since overnutrition, hyperglycemia, insulin resistance and obesity are associated with systemic low-grade chronic inflammation [21][22][23][24] , we investigated the expression levels of several common inflammatory cytokines in circulating leukocytes. The hyperglycemic sheep fed the HC diet showed increased expression levels of the The HC diet induced significant hepatic steatosis and hepatomegaly.…”
Section: Resultsmentioning
confidence: 99%
“…Since overnutrition, hyperglycemia, insulin resistance and obesity are associated with systemic low-grade chronic inflammation [21][22][23][24] , we investigated the expression levels of several common inflammatory cytokines in circulating leukocytes. The hyperglycemic sheep fed the HC diet showed increased expression levels of the The HC diet induced significant hepatic steatosis and hepatomegaly.…”
Section: Resultsmentioning
confidence: 99%
“…Although this model of maternal inflammation-induced IUGR, or MI-IUGR, produced milder fetal growth restriction than the hyperthermic PI-IUGR model, we found similar metabolic dysfunction and impaired muscle growth, as described in later sections. It should be noted that this model may be reflective of the chronic inflammatory conditions of maternal obesity (Yan et al, 2011a, 2011b; Ghnenis et al, 2017) and overeating (Jones et al, 2018), which produced both maternofetal inflammation and postnatal metabolic dysfunction.…”
Section: Sheep Models For Recapitulating Characteristics Of the Iugr mentioning
confidence: 99%
“…In addition to mounting a chronically-sustained “adrenaline rush,” late-term fetuses also respond to hypoxemia with increased systemic inflammation (Jones et al, 2018). When IUGR was induced in fetal sheep by hypoxemia, circulating levels of the inflammatory cytokines TNFα and IL-6 as well as prostaglandins and activin A were elevated (Bertucci et al, 2011).…”
Section: Pathologies Associated With Intrauterine Growth Restrictionmentioning
confidence: 99%
“…In IUGR animal models, TNFα and IL-6 are elevated in late gestation (Bertucci et al, 2011), and we recently reported that maternofetal inflammation due to maternal bacterial endotoxin injection at mid-gestation in rats results in smaller fetuses with increased circulating TNFα at term, well after maternal biomarkers of inflammation had subsided (Cadaret et al, 2017a). Reduced delivery of nutrients can also increase fetal biomarkers of inflammation late in gestation (Jones et al, 2018). The adrenergic and inflammatory systems mediate many of the physiological changes affecting growth and metabolism in the IUGR fetus, and one prominent mode of action is inhibition of growth factors.…”
Section: Iugr Fetal Pathophysiologymentioning
confidence: 99%